Advantages of the Green Solid State FSW over the Conventional GMAW Process - Hasan I. Dawood; Kahtan S. Mohammed; Mumtaz Y. Rajab (Advances in Materials Science and Engineering)
The present work is an experimental comparison between the friction stir welding (FSW) and the conventional gas metal arc welding (GMAW) in joining of Al alloys. Two sets of 3 mm thick aluminum strip pairs were friction stir welded in a regular butting joint configuration. Two rotational speeds of 1750 rpm and 2720 rpm were utilized to perform the FSW process. The axial force and the transverse speed were kept constant at 6.5 KN and 45 mm/min, respectively. Cylindrical tool shoulder and pin geometry were selected. Strip pairs of other similar sets were butt jointed using the conventional GMAW. The welding quality, power input, and macrostructure and microstructure of the butted joints were examined. The types of the fumes and the amount of the released gases were measured and compared. The results showed that the solid state FSW is green, environment-friendly, and of superior welding properties compared to the conventional GMAW.